Peningkatan Kemampuan Kognitif Melalui Bermain Eksperimen - Rini Herminastiti (Universitas Lampung, 2020)
This study aims to improve the cognitive abilities of early childhood aged 5-6 years through playing experiments in science at Nur Annisa Ciracas School, East Jakarta, the odd semester of the 2019/2020 school year. This research is a classroom action research. This research method is a classroom action research which refers to the model of Kemmis Taggart. This study consisted of II cycles where each cycle included 4 stages, namely planning, implementing, observing and reflecting. The research implementation time was 2 months, namely August and September with 12 students as research subjects, while the data were collected through observation, interview and observation. Based on the research results in cycle I and cycle II, there was an increase in cognitive abilities through playing science experiments. This is evidenced by the increase in the average value per class in cycle I = 60.06% and an increase of 20.14% in cycle II = 80.20% which has exceeded the 75% success criteria. This study concluded that playing science experiments can improve cognitive abilities in early childhood.Keywords: cognitive abilities, play experiments, science DOI: http://dx.doi.org/10.23960/jiip.v2i1.21790